2016
DOI: 10.4238/gmr.15038431
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone matrix gelatin/fibrin glue and chitosan/gelatin composite scaffolds for cartilage tissue engineering

Abstract: ABSTRACT. This study was designed to evaluate bone matrix gelatin (BMG)/fibrin glue and chitosan/gelatin composite scaffolds for cartilage tissue engineering. Chondrocytes were isolated from costal cartilage of Sprague-Dawley rats and seeded on BMG/fibrin glue or chitosan/gelatin composite scaffolds. After different in vitro culture durations, the scaffolds were subjected to hematoxylin and eosin, Masson's trichrome, and toluidine blue staining, anti-collagen II and anti-aggrecan immunohistochemistry, and scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Thrombin acts as an enzyme and converts the fibrogen into fibrin in about 10-60 s [31]. Fibrin glue has been used as a scaffold for a long time to culture a variety of cells and tissue analogues [31][32][33][34]. As a hydrogel, it has also been widely used in nerve tissue engineering to repair peripheral nervous system (PNS) injuries and CNS injuries [35,36].…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Thrombin acts as an enzyme and converts the fibrogen into fibrin in about 10-60 s [31]. Fibrin glue has been used as a scaffold for a long time to culture a variety of cells and tissue analogues [31][32][33][34]. As a hydrogel, it has also been widely used in nerve tissue engineering to repair peripheral nervous system (PNS) injuries and CNS injuries [35,36].…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate otologic tissue engineering 15,25‐35,38‐43,45,46,107‐144 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Filardo et al (24) showed improvement in postoperative scaffold stability and integrity using fibrin glue. Wang et al (25), however, reported that a bone matrix gelatin and fibrin glue scaffold showed signs of degradation after 8 weeks despite the presence of supporting chondrocyte attachment, proliferation, and biosynthesis of cartilaginous matrix components. Another study proposed that fibrin sealant supports the migration and proliferation of human chondrocytes via thrombin (26).…”
Section: Amic Microfracturing Osteochondral Defects Osteochondrosis Dmentioning
confidence: 99%